Fade to black - Stevens, Amanda; Mills & Boon Series Special Releases (Sydney, New South Wales : HarperCollins Publishers, 2021)
Making up for lost time... Pierce Kincaid couldn't understand why his wife nearly fainted when he came home from the store - or why she is no longer pregnant...until a five-year-old boy asks Mummy who the stranger is. Terror-filled nightmares slowly reveal that the ex-secret agent had been kidnapped, his memory wiped clean. Pierce knows that Jessica still loves him. But if he wants a second chance at the life he lost, he'll need to discover the truth behind his abduction and take down the kidnappers targeting his family - before death truly does part them. Originally published in 1995.
Keywords: Families -- Fiction; Pregnancy -- Fiction; Secrets -- Fiction; Contemporary romance; Fiction - Romance - Contemporary; Fiction - Romance - General; Australian; Electronic books